The Role of Architecture in Post-Conflict Spaces: the Case of the City of Mostar (Proceedings of Faculty of Civil Engineering, 2022)
Post-conflict spaces are defined by the complex and difficult burden of the war past, national conflicts and unresolved political issues. Those are now spaces without war, yet without real peace. The research deals with the city of Mostar and the repercussions of war divisions on its urban structure. By using Mostar as case study, the paper detects challenges and potential strategies of architectural and planning practice within post-conflict environments, as well as their role in the postwar recovery.
Keywords: Mostar; division; conflict; boundary; urban planning